2018
DOI: 10.21547/jss.408090
|View full text |Cite
|
Sign up to set email alerts
|

Investıgatıon Of The Factors Affectıng Man's Use To Physıcal Vıolence To Women

Abstract: Bu araştırmada kadına fiziksel şiddet uygulamış ve uygulamamış erkeklerin toplumsal cinsiyet tutumları ile şiddet uygulamaları arasındaki ilişkinin ve şiddet uygulamaya etki eden diğer faktörlerin incelenmesi amaçlanmıştır. Araştırma Merkezefendi Devlet Hastanesi'nde çalışan erkek personel ile hastaneye başvuran erkek hastalarla yapılmıştır. Toplamda 386 erkek ile yapılmış nicel ve genel tarama modeline (tekil ve ilişkisel) dayalı bir araştırmadır. Araştırmada katılımcılara ilişkin sosyo-demografik bilgiler, ç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…The present study determined that pregnant women who were employed and had a moderate income were exposed to lower level of violence. Previous studies also found that unemployed pregnant women with low socioeconomic status were exposed to more violence (Akkuş & Yıldırım, 2018). In addition, this study determined that pregnant women whose husbands were self‐employed were exposed to higher levels of violence compared to those whose husbands were workers and civil servants.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The present study determined that pregnant women who were employed and had a moderate income were exposed to lower level of violence. Previous studies also found that unemployed pregnant women with low socioeconomic status were exposed to more violence (Akkuş & Yıldırım, 2018). In addition, this study determined that pregnant women whose husbands were self‐employed were exposed to higher levels of violence compared to those whose husbands were workers and civil servants.…”
Section: Discussionmentioning
confidence: 84%
“…The present study found that those who run away and secretly got married were exposed to higher level of violence than those who had a prearranged marriage and those who married out of love. Other Turkish studies have also reported that those who married out of love are exposed to lower level of violence than those with other types of marriage (Akkuş & Yıldırım, 2018;Şahin & Dündar, 2017). In elopements, women do not receive positive parental support.…”
Section: Discussionmentioning
confidence: 93%
“…It has been determined that men are more prone to perpetrating violence during the quarantine period than are women (p<0.05). Given gender roles in our country, Turkey, men think that they are dominant in family relationships, and thus they are to assume the breadwinning and protecting roles [31]. During the COVID-19 pandemic, men's spending relatively more time at home, the emergence of existing social and economic problems, anxiety for the future, and though partly, loss of bread winning and protecting roles have caused them to display a favorable attitude towards violence [30,32].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on the determinants of domestic violence, women whose spouses had secondary or higher education were 48% less likely to experience domestic violence than women whose spouses had no education [29]. According to Akkus ¸et al, the level of violence committed by men against their spouses increased with the decrease in the level of their education [30]. Hence, the level of education influences violence.…”
Section: Discussionmentioning
confidence: 99%